Nickel-based superalloy and powder, TiC-doped nickel-based superalloy and powder as well as preparation and application of nickel-based superalloy and powder
By reasonably controlling the elemental composition of nickel-based high-temperature alloy powder, its crack resistance and printing performance are improved, and the problem of insufficient crack resistance of existing nickel-based high-temperature alloy powders is solved, and excellent mechanical properties suitable for high-temperature components are achieved.
Patent Information
- Application Number
- CN202411932671.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-18
AI Technical Summary
The crack resistance of existing nickel-based high-temperature alloy powders needs to be improved.
By reasonably controlling the elemental composition of nickel-based high-temperature alloy powder, the content of γ'forming element Al+Ti is controlled, and the content of Ta is increased to reduce the tendency of thermal cracking between dendrites. At the same time, the content of Co is designed to control the content of the alloy to reduce the layer error energy.
The printing performance of nickel-based high-temperature alloy powder is improved and the crack density is reduced, so that the obtained nickel-based high-temperature alloy has excellent mechanical properties and is suitable for high-temperature components.
Smart Images

Figure CN119640095A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy materials, and in particular to a nickel-based high-temperature alloy and powder, a TiC-doped nickel-based high-temperature alloy and powder, and preparation and application thereof. Background Art
[0002] Nickel-based superalloys play a key role in high-temperature applications in aerospace, energy, and chemical industries due to their excellent high-temperature strength, oxidation resistance, and hot corrosion resistance. These alloys are widely used in key parts such as hot end components of gas turbines, turbine blades and guide vanes of aircraft engines, etc.
[0003] The crack resistance of the nickel-based high-temperature alloy powder provided in the prior art needs to be further improved. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a nickel-based high-temperature alloy and powder, a TiC-doped nickel-based high-temperature alloy and powder, and a preparation method and application thereof. The nickel-based high-temperature alloy powder provided by the present invention has good crack resistance.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The invention provides a nickel-based high-temperature alloy powder, comprising the following elements in percentage by mass: 8-10% Cr, 13-17% Co, 2-5% Al, 4-5% W, 4-5% Mo, 1-2% Ti, 6-8% Ta, 0.005-0.1% C, 0.005-0.1% B and the balance Ni.
[0007] The present invention also provides a method for preparing the nickel-based high-temperature alloy powder described in the above technical solution, comprising the following steps:
[0008] The raw materials are subjected to vacuum smelting to obtain alloy liquid;
[0009] The alloy liquid is subjected to gas atomization treatment and screening to obtain the nickel-based high-temperature alloy powder.
[0010] The present invention also provides a nickel-based high-temperature alloy, which is prepared from the nickel-based high-temperature alloy powder described in the above technical solution or the nickel-based high-temperature alloy powder prepared by the preparation method described in the above technical solution.
[0011] The present invention also provides a method for preparing the nickel-based high-temperature alloy described in the above technical solution, comprising the following steps:
[0012] The nickel-based high-temperature alloy powder described in the above technical solution or the nickel-based high-temperature alloy powder prepared by the preparation method described in the above technical solution is used as a raw material, and the nickel-based high-temperature alloy is obtained by laser selective melting molding or laser coaxial powder feeding molding.
[0013] The present invention also provides a TiC-doped nickel-based high-temperature alloy powder, comprising a nickel-based high-temperature alloy powder and a titanium carbide powder; the nickel-based high-temperature alloy powder is the nickel-based high-temperature alloy powder described in the above technical solution or the nickel-based high-temperature alloy powder prepared by the preparation method described in the above technical solution.
[0014] Preferably, the mass of the titanium carbide powder is 0-2% of the mass of the nickel-based high-temperature alloy powder, but not 0%.
[0015] The present invention also provides a method for preparing the TiC-doped nickel-based high-temperature alloy powder described in the above technical solution, comprising the following steps:
[0016] The nickel-based high-temperature alloy powder and the titanium carbide powder are mixed at high frequency to obtain the TiC-doped nickel-based high-temperature alloy powder;
[0017] The acceleration of the high-frequency mixing is 50-100g, and the vibration frequency is 50-60Hz.
[0018] The present invention also provides a TiC-doped nickel-based high-temperature alloy, which is prepared from the TiC-doped nickel-based high-temperature alloy powder described in the above technical solution or the TiC-doped nickel-based high-temperature alloy powder prepared by the preparation method described in the above technical solution.
[0019] The present invention also provides a method for preparing the TiC-doped nickel-based high-temperature alloy described in the above technical solution, using the TiC-doped nickel-based high-temperature alloy powder described in the above technical solution or the TiC-doped nickel-based high-temperature alloy powder obtained by the preparation method described in the above technical solution as a raw material, and performing laser selective melting molding or laser coaxial powder feeding molding to obtain the TiC-doped nickel-based high-temperature alloy.
[0020] The present invention also provides the use of the nickel-based high-temperature alloy powder, the nickel-based high-temperature alloy, the TiC-doped nickel-based high-temperature alloy powder or the TiC-doped nickel-based high-temperature alloy described in the above technical solution in the fields of aerospace, aviation or energy.
[0021] The invention provides a nickel-based high-temperature alloy powder, comprising the following elements in percentage by mass: 8-10% Cr, 13-17% Co, 2-5% Al, 4-5% W, 4-5% Mo, 1-2% Ti, 6-8% Ta, 0.005-0.1% C, 0.005-0.1% B and the balance Ni.
[0022] The present invention reasonably controls the element composition of the nickel-based high-temperature alloy powder, controls the content of γ'-forming elements Al+Ti that are unfavorable to printing processability, and maintains them at an appropriate level. At the same time, in order to ensure that there are sufficient strengthening phases in the alloy, the content of another γ'-forming element Ta is appropriately increased. The Ta element can improve the material properties while reducing the thermal cracking tendency between dendrites during solidification. In addition, the present invention controls the content of the Co element by design to reduce the stacking fault energy of the alloy and improve the crack sensitivity of the alloy additive manufacturing. Therefore, the printing performance of the nickel-based high-temperature alloy powder is comprehensively improved, so that the crack density of the nickel-based high-temperature alloy prepared by using the nickel-based high-temperature alloy powder is small.
[0023] The present invention also provides a TiC-doped nickel-based high-temperature alloy powder. The present invention mixes titanium carbide with the nickel-based high-temperature alloy powder, further improving the printing performance of the nickel-based high-temperature alloy, so that the obtained titanium carbide-doped nickel-based high-temperature alloy has almost no cracks and has excellent mechanical properties, and is suitable for high-temperature parts in the fields of aerospace, aviation or energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope photograph of the printed sample of the laser selective melting nickel-based high-temperature alloy obtained in Example 1;
[0025] Figure 2 The room temperature tensile stress-strain curve of the printed sample of the nickel-based high-temperature alloy formed by laser selective melting obtained in Example 1;
[0026] Figure 3 This is a scanning electron microscope photograph of the printed sample of the nickel-based high-temperature alloy formed by laser selective melting obtained in Example 2;
[0027] Figure 4 The room temperature tensile stress-strain curve of the printed sample of the laser selective melting nickel-based high-temperature alloy obtained in Example 2
[0028] Figure 5 This is a SEM image of the first TiC-doped nickel-based high-temperature alloy powder obtained in Example 3;
[0029] Figure 6 This is a light microscopic photograph of the printed sample of the TiC-doped nickel-based high-temperature alloy formed by laser selective melting obtained in Example 3;
[0030] Figure 7 This is a scanning electron microscope photograph of the printed sample of the TiC-doped nickel-based high-temperature alloy formed by laser selective melting obtained in Example 3;
[0031] Figure 8 The room temperature tensile stress-strain curve of the printed sample of the TiC-doped nickel-based high-temperature alloy formed by laser selective melting obtained in Example 3;
[0032] Fig. 9 This is a light microscopic photograph of the printed sample of the TiC-doped nickel-based high-temperature alloy formed by laser coaxial powder feeding obtained in Example 3;
[0033] Fig.10 The room temperature tensile stress-strain curve of the printed sample of the TiC-doped nickel-based high-temperature alloy formed by laser coaxial powder feeding obtained in Example 3;
[0034] Fig.11 This is a scanning electron microscope photograph of the printed sample of the TiC-doped nickel-based high-temperature alloy formed by laser selective melting obtained in Example 4;
[0035] Fig.12 This is a scanning electron microscope photograph of the printed sample of the TiC-doped nickel-based high-temperature alloy formed by laser selective melting obtained in Example 5. DETAILED DESCRIPTION
[0036] The invention provides a nickel-based high-temperature alloy powder, comprising the following elements in percentage by mass: 8-10% Cr, 13-17% Co, 2-5% Al, 4-5% W, 4-5% Mo, 1-2% Ti, 6-8% Ta, 0.005-0.1% C, 0.005-0.1% B and the balance Ni.
[0037] Unless otherwise specified, the raw materials used in the present invention are preferably commercially available products.
[0038] In terms of mass percentage, the nickel-based high-temperature alloy powder provided by the present invention comprises 8-10% Cr, and is preferably 8%, 8.5%, 9%, 9.5% or 10%. In the present invention, Cr plays a role in solid solution strengthening and can ensure the oxidation resistance and corrosion resistance of the alloy.
[0039] Based on the mass percentage of Cr, the nickel-based high-temperature alloy powder provided by the present invention includes Co13-17%, and is preferably 13%, 13.5%, 14%, 14.5%, 15%, 15.5%, 16%, 16.5% or 17%. In the present invention, Co plays a role in solid solution strengthening, increases the solid solution temperature of the alloy, and at the same time, the increase in Co content can reduce the stacking fault energy of the alloy, which is beneficial to improving the additive manufacturing printing processability of the alloy.
[0040] Based on the mass percentage of Cr, the nickel-based high-temperature alloy powder provided by the present invention includes 2-5% Al, and is preferably 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%. In the present invention, Al is a γ' strengthening phase forming element, and the addition of Al can improve the strength of the alloy, but too much Al is not conducive to increasing the crack sensitivity of the alloy, and the addition amount of Al element should be controlled to be 2-5%.
[0041] Based on the mass percentage of Cr, the nickel-based high-temperature alloy powder provided by the present invention includes W4-5%, preferably 4%, 4.2%, 4.4%, 4.5%, 4.6%, 4.8% or 5%. In the present invention, W can play a good solid solution strengthening role, and an appropriate amount of W is conducive to reducing the crack sensitivity of the alloy.
[0042] Based on the mass percentage of Cr, the nickel-based high-temperature alloy powder provided by the present invention includes 4-5% Mo, and is preferably 4%, 4.2%, 4.4%, 4.5%, 4.6%, 4.8% or 5%. In the present invention, Mo can play a good role in solid solution strengthening.
[0043] Based on the mass percentage of Cr, the nickel-based high-temperature alloy powder provided by the present invention includes 1-2% Ti, and is preferably 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8% or 2%. In the present invention, the mass ratio of Ti to Al (Ti / Al ratio) is preferably 0.2-0.5:1, and is preferably 0.2:1, 0.3:1, 0.4:1 or 0.5:1. In the present invention, the total mass percentage of Ti and Al is preferably 4-6%, and is preferably 4%, 5% or 6%. In the present invention, Ti is a γ' strengthening phase forming element. The addition of Ti can promote the formation of γ' phase and improve the strength of the alloy, but too much Ti will reduce the high-temperature microstructure stability. Therefore, the amount of Ti added should be controlled and a certain Ti / Al ratio should be guaranteed.
[0044] Based on the mass percentage of Cr, the nickel-based high-temperature alloy powder provided by the present invention includes Ta 6-8%, and is preferably 6%, 6.5%, 6.8%, 7%, 7.5%, 7.8% or 8%. In the present invention, Ta can play a good precipitation strengthening effect, and the addition of Ta element can reduce the thermal cracking tendency between dendrites during solidification. When the addition amount of Al and Ti elements is controlled, the addition of Ta can ensure that there is a sufficient content of γ' strengthening phase in the alloy.
[0045] Based on the mass percentage of Cr, the nickel-based high-temperature alloy powder provided by the present invention includes 0.005-0.1% C, and is preferably 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09% or 0.1%. In the present invention, C can play a role in grain boundary strengthening by forming carbides.
[0046] Based on the mass percentage of Cr, the nickel-based high-temperature alloy powder provided by the present invention includes B0.005-0.1%, and is preferably 0.005%, 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09% or 0.1%. In the present invention, B can play a good role in grain boundary strengthening by forming borides.
[0047] Based on the mass percentage of Cr, the nickel-based high-temperature alloy powder provided by the present invention includes a balance of Ni.
[0048] The present invention also provides a method for preparing the nickel-based high-temperature alloy powder described in the above technical solution, comprising the following steps:
[0049] The raw materials are subjected to vacuum smelting to obtain alloy liquid;
[0050] The alloy liquid is subjected to gas atomization treatment and screening to obtain the nickel-based high-temperature alloy powder.
[0051] The present invention performs vacuum smelting on the raw materials to obtain alloy liquid. In the present invention, the vacuum degree of the vacuum smelting is preferably 0.06-10Pa, and specifically preferably 0.06Pa, 0.1Pa, 0.5Pa, 1Pa, 5Pa or 10Pa. In the present invention, the vacuum smelting is preferably performed under a protective atmosphere, and the protective atmosphere is preferably an inert atmosphere, and the inert atmosphere preferably includes argon, and the purity of the inert atmosphere is preferably greater than or equal to 99.9%.
[0052] After obtaining the alloy liquid, the present invention subjects the alloy liquid to aerosol treatment and screening to obtain the nickel-based high-temperature alloy powder. In the present invention, the parameters of the aerosol treatment include: the nozzle diameter is preferably 4 mm; the aerosol pressure is preferably 4 to 10 MPa, and specifically preferably 4 MPa, 5 MPa, 6 MPa, 7 MPa, 8 MPa, 9 MPa or 10 MPa; the time is preferably 5 to 15 min, and specifically preferably 5 min, 10 min, 12 min or 15 min. The present invention does not specifically limit the screening operation, as long as the nickel-based high-temperature alloy powder of the target particle size can be obtained. In the present invention, the aerosol treatment is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably argon, and the purity of the argon is preferably 99.9%.
[0053] The present invention also provides a nickel-based high-temperature alloy, which is prepared from the nickel-based high-temperature alloy powder described in the above technical solution or the nickel-based high-temperature alloy powder prepared by the preparation method described in the above technical solution.
[0054] The present invention also provides a method for preparing the nickel-based high-temperature alloy described in the above technical solution, comprising the following steps:
[0055] The nickel-based high-temperature alloy powder described in the above technical solution or the nickel-based high-temperature alloy powder prepared by the preparation method described in the above technical solution is used as a raw material, and the nickel-based high-temperature alloy is obtained by laser selective melting molding or laser coaxial powder feeding molding.
[0056] In the present invention, the nickel-based high-temperature alloy powder is preferably dried before laser selective melting molding or laser coaxial powder feeding molding. The drying treatment is preferably vacuum drying. The vacuum drying temperature is preferably 120-150°C, more preferably 130-140°C, and the time is preferably 1-3h, more preferably 2h. After the drying treatment, the present invention preferably also includes cooling to room temperature in a box.
[0057] In the present invention, the parameters of the laser selective melting molding include: the particle size of the nickel-based high-temperature alloy powder is preferably 15-53 μm, the laser power is 215-335 W, and specifically preferably 215 W, 250 W, 275 W, 300 W, 315 W or 335 W; the scanning rate is 800-1100 mm / s, and specifically preferably 800 mm / s, 850 mm / s, 900 mm / s, 950 mm / s, 1000 mm / s, 1050 mm / s, mm / s or 1100mm / s; the thickness of the powder layer is 30-60μm, preferably 30μm, 35μm, 40μm, 45μm, 50μm, 55μm or 60μm; the scanning interval is 80-120μm, preferably 80μm, 85μm, 90μm, 95μm, 100μm, 105μm, 110μm, 115μm or 120μm; the scanning mode is a strip scanning mode, and each layer is rotated 67° after scanning. In the present invention, the laser selective melting molding is preferably carried out under a protective atmosphere, and the protective atmosphere is preferably argon, the purity of the argon is preferably ≥99.99%, and the oxygen content is preferably <350ppm.
[0058] In the present invention, the parameters of the laser coaxial powder feeding forming include: the particle size of the nickel-based high-temperature alloy powder is 53-150 μm, the laser power is 1800-2200 W, and is preferably 1800 W, 1850 W, 1900 W, 1950 W, 2000 W, 2050 W, 2100 W, 2150 W or 2200 W; the scanning rate is 720-960 mm / min, and is preferably 720 mm / min, 740 mm / min, 750 mm / min, 760 mm / min, 780 mm / min, 800 mm / min, 820 mm / min, 840 mm / min, 850 mm / min, 860 mm / min, 870 mm / min, 880 mm / min, 890 mm / min, 900 mm / min, 910 mm / min, 920 mm / min, 930 mm / min, 940 mm / min, 950 mm / min, 960 mm / min, 970 mm / min, 980 mm / min, 990 mm / min, 1000 mm / min, 1010 mm / min, 1020 mm / min, 1030 mm / min, 1040 mm / min, 1050 mm / min, 1060 mm / min, 1070 mm / min, 1080 mm / min, 1090 mm / min, 1100 mm / min, 1110 mm / min, 1120 mm / min, 1130 mm / min, 1140 mm / min, 1150 mm / min, 1160 mm / min, 1170 mm / min 60mm / min, 880mm / min, 900mm / min, 920mm / min, 940mm / min, 950mm / min or 960mm / min; the powder feeding amount is 10-14g / min, and specifically preferably 10g / min, 11g / min, 12g / min, 13g / min or 14g / min; the overlap width is 1-1.6mm, and specifically preferably 1mm, 1.1mm, 1.2mm, 1.3mm, 1.4mm, 1.5mm or 1.6mm; the spot diameter is 0.5-3mm, and specifically preferably 0.5mm, 1mm, 1.5mm, 2mm, 2.5mm or 3mm.
[0059] In the present invention, the laser selective melting forming or laser coaxial powder feeding forming preferably also includes a forming substrate, and the material of the forming substrate is preferably 304 stainless steel. In the present invention, the forming substrate is preferably pretreated before use, and the pretreatment preferably includes the following steps: sandblasting, washing, drying and preheating in sequence; the present invention does not specifically limit the sandblasting method, and the sandblasting method well known to those skilled in the art can be used; the washing preferably includes acetone washing and ethanol washing in sequence, and the present invention does not specifically limit the acetone washing and ethanol washing, as long as the debris on the surface of the forming substrate can be removed. In the present invention, the preheating temperature is preferably 110-130°C, and more preferably 120°C.
[0060] The present invention also provides a TiC-doped nickel-based high-temperature alloy powder, comprising a nickel-based high-temperature alloy powder and a titanium carbide powder; the nickel-based high-temperature alloy powder is the nickel-based high-temperature alloy powder described in the above technical solution or a nickel-based high-temperature alloy powder prepared by the preparation method described in the above technical solution.
[0061] In the present invention, the particle size of the nickel-based high-temperature alloy powder is preferably 15 to 150 μm, and specifically preferably 15 to 53 μm or 53 to 150 μm.
[0062] In the present invention, the particle size of the titanium carbide powder is preferably 20 to 50 nm.
[0063] In the present invention, the mass of the titanium carbide powder is preferably 0-2% of the mass of the nickel-based high-temperature alloy powder, not 0%, and is specifically preferably 0.5%, 1%, 1.5% or 2%. The present invention controls the mass of the titanium carbide powder to be 0-2% of the mass of the nickel-based high-temperature alloy powder, which can effectively improve the printing performance of the nickel-based high-temperature alloy powder and prevent agglomeration caused by excessive TiC content, so that the precipitated second phase becomes coarse.
[0064] The present invention also provides a method for preparing the TiC-doped nickel-based high-temperature alloy powder described in the above technical solution, comprising the following steps:
[0065] The nickel-based high-temperature alloy powder and the titanium carbide powder are mixed at high frequency to obtain the TiC-doped nickel-based high-temperature alloy powder;
[0066] The acceleration of the high-frequency mixing is 50-100g, and the vibration frequency is 50-60Hz.
[0067] In the present invention, the acceleration of the high-frequency mixing is 50-100g, and is preferably 50g, 55g, 60g, 65g, 70g, 75g, 80g, 85g, 90g, 95g or 100g; the vibration frequency is 50-60Hz, and is preferably 50Hz, 51Hz, 52Hz, 53Hz, 54Hz, 55Hz, 56Hz, 57Hz, 58Hz, 59Hz or 60Hz. In the present invention, the time of the high-frequency mixing is preferably 1-3min.
[0068] In the present invention, the high-frequency mixing is preferably carried out in a high-frequency powder mixing device.
[0069] In the present invention, the high-frequency mixing allows the nickel-based high-temperature alloy and titanium carbide to be fully mixed, and can also improve the printing performance of the nickel-based high-temperature alloy powder.
[0070] The present invention also provides a TiC-doped nickel-based high-temperature alloy, which is prepared from the TiC-doped nickel-based high-temperature alloy powder described in the above technical solution or the TiC-doped nickel-based high-temperature alloy powder prepared by the preparation method described in the above technical solution.
[0071] The present invention also provides a method for preparing the TiC-doped nickel-based high-temperature alloy described in the above technical solution, using the TiC-doped nickel-based high-temperature alloy powder described in the above technical solution or the TiC-doped nickel-based high-temperature alloy powder obtained by the preparation method described in the above technical solution as a raw material, and performing laser selective melting molding or laser coaxial powder feeding molding to obtain the TiC-doped nickel-based high-temperature alloy.
[0072] In the present invention, the parameters of the laser selective melting molding or laser coaxial powder feeding molding are preferably consistent with the above technical solution, which will not be described in detail here.
[0073] The present invention also provides the use of the nickel-based high-temperature alloy powder, the nickel-based high-temperature alloy, the TiC-doped nickel-based high-temperature alloy powder or the TiC-doped nickel-based high-temperature alloy described in the above technical solution in the fields of aerospace, aviation or energy.
[0074] In the present invention, the nickel-based high-temperature alloy powder and the nickel-based high-temperature alloy powder doped with TiC have excellent printing performance. The nickel-based high-temperature alloy and the nickel-based high-temperature alloy doped with TiC have low crack sensitivity and good mechanical properties, and are suitable for high-temperature parts manufactured by additive manufacturing in the fields of aerospace, aviation, and energy.
[0075] The nickel-based high-temperature alloy and powder, TiC-doped nickel-based high-temperature alloy and powder, and preparation methods and applications thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0076] In the following embodiments, the parameters of laser selective melting molding include: laser power of 335W, scanning rate of 1000mm / s, scanning spacing of 100μm, and powder layer thickness of 40μm; laser selective melting molding is carried out in a closed chamber under the protection of high-purity argon (argon purity ≥99.99%, oxygen content <350ppm), wherein the scanning mode is a strip scanning mode, and each layer is rotated 67° after scanning.
[0077] The parameters of laser coaxial powder feeding forming include: laser power of 1800W, scanning rate of 720mm / min, powder feeding amount of 11g / min, overlap width of 1.3mm, and spot diameter of 2mm.
[0078] Example 1
[0079] The nickel-based high-temperature alloy powder has an elemental composition, by mass percentage, of Cr 8%, Co 15%, Al 4%, W4%, Mo 4%, Ti 2%, Ta 6%, C 0.1%, B 0.015% and Ni balance, wherein the mass ratio of Ti to Al is 0.5:1, and the total mass percentage of Ti and Al is 6%.
[0080] Preparation method of nickel-based high-temperature alloy powder: prepare the raw materials according to the composition of the above nickel-based high-temperature alloy powder, place the raw materials in a smelting furnace, evacuate to below 10Pa, perform vacuum smelting, and obtain alloy liquid.
[0081] The alloy liquid was sprayed into an atomizing tower using a graphite nozzle with a diameter of 4 mm. The atomizing tower was filled with argon gas with a purity of 99.9% as a protective atmosphere. The atomization treatment was carried out for 12 minutes under an atomization pressure of 8 MPa. During the atomization treatment, the alloy liquid was crushed by argon gas and cooled to obtain alloy powder.
[0082] The obtained alloy powder was sieved by a powder sieving machine to obtain nickel-based high-temperature alloy powder with a particle size of 15 to 53 μm (subsequently used for laser selective melting forming) and nickel-based high-temperature alloy powder with a particle size of 53 to 150 μm (subsequently used for laser coaxial powder feeding).
[0083] The nickel-based high-temperature alloy powder with a particle size of 15 to 53 μm is placed in a drying oven, heated to 130°C in a vacuum environment for drying for 2 hours, and then cooled in the oven and the obtained dry alloy powder is added to the powder feeding cylinder of the laser selective melting equipment.
[0084] The molding substrate is 304 stainless steel. The upper surface of the molding substrate is sandblasted in advance with a sandblasting machine and cleaned with acetone to remove surface debris. It is then cleaned with ethanol and blown dry. The dried molding substrate is mounted on the molding platform and leveled, and then preheated to 120°C.
[0085] The laser selective melting forming equipment was turned on and the laser selective melting forming parameters were set to obtain a laser selective melting formed nickel-based high-temperature alloy printed sample.
[0086] Figure 1 This is a scanning electron microscope photo of the printed sample of the laser selective melting nickel-based superalloy. Figure 1 It can be seen that the laser selective melting structure of the alloy is a typical cellular dendrite structure. Microcracks can be observed in some areas, and the crack length does not exceed 100μm. Overall, the crack density in the printed alloy structure is low, and the crack density does not exceed 0.2mm / mm 2 , and there are fewer defects such as holes, and the density can reach more than 99.7%, so the nickel-based high-temperature alloy powder has good printing processability.
[0087] GB / T 228.1-2021 was used to test the room temperature tensile stress and strain of the printed samples of the laser selective melting nickel-based high-temperature alloy. The results are as follows: Figure 2 As shown, Figure 2 The room temperature tensile stress-strain curve of the printed sample of the laser selective melting nickel-based superalloy is shown in Figure 2. Figure 2 It can be seen that the room temperature tensile strength is 1462MPa, the yield strength is 1010MPa, and the room temperature elongation is 15.7%. It has high tensile strength and elongation and excellent room temperature tensile properties.
[0088] Example 2
[0089] The only difference from Example 1 is that the element composition of the nickel-based high-temperature alloy powder, calculated by mass percentage, includes: Cr 8%, Co 15%, Al 5%, W4%, Mo 4%, Ti 1%, Ta 7%, C 0.05%, B 0.01% and Ni balance, and the preparation method is the same as Example 1, wherein the mass ratio of Ti to Al is 0.2:1, and the total mass percentage of Ti and Al is 6%.
[0090] Figure 3 This is a light microscope photo of the printed sample of the laser selective melting nickel-based superalloy. Figure 3 It can be seen that there are only trace cracks and holes in the printed structure, and the number of defects is very small, indicating that the printing processability of nickel-based high-temperature alloy powder is good.
[0091] The room temperature tensile stress and strain of the printed sample of the laser selective melting nickel-based high-temperature alloy obtained by the method of Example 1 were tested. The results are as follows: Figure 4 , Figure 4 The room temperature tensile stress-strain curve of the printed sample of the laser selective melting nickel-based superalloy is shown in Figure 2. Figure 4 It can be seen that the room temperature tensile strength is 1285MPa and the room temperature elongation is 17.7%, which has excellent room temperature tensile properties.
[0092] Example 3
[0093] The nickel-based high-temperature alloy powder with a particle size of 15 to 53 μm and the TiC powder (particle size of 20 to 50 nm, the mass of the TiC powder being 1% of the mass of the nickel-based high-temperature alloy powder) obtained in Implementation 1 are fully mixed in a high-frequency powder mixing device (acceleration of 100 g, vibration frequency of 60 Hz) to obtain a first nickel-based high-temperature alloy powder doped with TiC.
[0094] The nickel-based high-temperature alloy powder with a particle size of 53 to 150 μm and the TiC powder (particle size of 20 to 50 nm, the mass of the TiC powder being 1% of the mass of the nickel-based high-temperature alloy powder) obtained in Example 1 are fully mixed in a high-frequency powder mixing device (acceleration of 100 g, vibration frequency of 60 Hz) to obtain a second nickel-based high-temperature alloy powder doped with TiC.
[0095] Figure 5 The SEM image of the first TiC-doped nickel-based high-temperature alloy powder obtained. Figure 5 It can be seen that the particle size of the first TiC-doped nickel-based high-temperature alloy powder is relatively uniform.
[0096] The first TiC-doped nickel-based high-temperature alloy powder is used as a material for laser selective melting to prepare a TiC-doped nickel-based high-temperature alloy formed by laser selective melting, which specifically includes the following steps:
[0097] The first TiC-doped nickel-based high-temperature alloy powder is placed in a drying oven, heated to 130° C. in a vacuum environment for drying for 2 hours, then cooled in the oven and the obtained dry alloy powder is added to the powder feeding cylinder of the laser selective melting equipment.
[0098] The molding substrate is 304 stainless steel. The upper surface of the molding substrate is sandblasted in advance with a sandblasting machine and cleaned with acetone to remove surface debris. It is then cleaned with ethanol and blown dry. The dried molding substrate is mounted on the molding platform and leveled, and then preheated to 120°C.
[0099] The laser selective melting forming equipment was turned on and the laser selective melting forming parameters were set to obtain a printed sample of a TiC-doped nickel-based high-temperature alloy formed by laser selective melting.
[0100] Figure 6 This is an optical microscopic photograph of the printed sample of the TiC-doped nickel-based high-temperature alloy formed by laser selective melting. The results show that there are fewer cracks and holes under the optical microscope, which confirms the good printability of the TiC-doped nickel-based high-temperature alloy powder.
[0101] Figure 7 This is a scanning electron microscope photo of a printed sample of a TiC-doped nickel-based superalloy formed by laser selective melting. Figure 7 It can be seen that the printed structure is a typical cellular dendrite structure, and no obvious cracks are observed in the sample, that is, the TiC-doped nickel-based high-temperature alloy powder has excellent printing performance.
[0102] Figure 8 The room temperature tensile stress-strain curve of the printed sample of TiC-doped nickel-based superalloy formed by laser selective melting. Figure 8 It can be seen that the room temperature tensile strength is 1356 MPa and the room temperature elongation is 21.3%, which has excellent room temperature tensile properties.
[0103] The second TiC-doped nickel-based high-temperature alloy powder is used as a material for laser coaxial powder feeding forming to prepare a TiC-doped nickel-based high-temperature alloy by laser coaxial powder feeding forming, which specifically includes the following steps:
[0104] The second TiC-doped nickel-based high-temperature alloy powder is placed in a drying oven, heated to 130° C. in a vacuum environment for drying for 2 hours, then cooled in the oven and the obtained dry alloy powder is added to the powder feeding cylinder of the laser coaxial powder feeding device;
[0105] The molding substrate is preferably a 304 stainless steel substrate; the molding substrate is pretreated before use, and the pretreatment includes: sandblasting the upper surface of the molding substrate with a sandblaster in advance, washing with acetone to remove surface debris, and then washing with alcohol and drying. After the molding substrate is placed in the printing cabin, the cabin door is closed and the air is washed to reduce the water and oxygen content to below 10ppm. After the air washing is completed, the laser is focused on the appropriate position of the molding substrate using the handwheel mode, and the parameters of the laser coaxial powder feeding molding are input to obtain the laser coaxial powder feeding molding TiC doped nickel-based high-temperature alloy printed sample.
[0106] Fig. 9 This is a light microscope photo of the printed sample of the TiC-doped nickel-based superalloy formed by laser coaxial powder feeding. Fig. 9 It can be seen that no cracks were found in the printed structure, only a small number of holes, indicating that the TiC-doped nickel-based high-temperature alloy powder has excellent printability using the laser coaxial powder feeding process.
[0107] The room temperature tensile stress and strain of the printed sample of the TiC-doped nickel-based high-temperature alloy obtained by laser coaxial powder feeding molding was tested using the method of Example 1. The results are as follows: Fig.10 As shown, Fig.10 The room temperature tensile stress-strain curve of the printed sample of TiC-doped nickel-based superalloy formed by laser coaxial powder feeding. Fig.10 It can be seen that the TiC-doped nickel-based high-temperature alloy powder has high tensile strength and elongation, specifically, the tensile strength is 1402 MPa, the elongation is 19.2%, and it has excellent room temperature tensile properties.
[0108] Example 4
[0109] The difference from Example 3 is that the mass of titanium carbide is 0.5wt% of the mass of the nickel-based high-temperature alloy powder, and the first nickel-based high-temperature alloy powder doped with TiC is obtained. According to the laser selective melting molding of Example 3, the nickel-based high-temperature alloy doped with TiC is obtained by laser selective melting molding.
[0110] Fig.11 This is a scanning electron microscope photo of the printed sample of the TiC-doped nickel-based high-temperature alloy formed by laser selective melting obtained in Example 4. Fig.11 It can be seen that: no cracks are still observed, that is, the TiC-doped nickel-based high-temperature alloy powder has excellent printing performance.
[0111] The room temperature tensile stress and strain of the printed sample of the TiC-doped nickel-based high-temperature alloy formed by selective laser melting was tested by the method of Example 1. The results showed that the tensile strength of the printed sample of the TiC-doped nickel-based high-temperature alloy formed by selective laser melting was 1537 MPa, and the elongation was 12.1%.
[0112] Example 5
[0113] The difference from Example 3 is that the mass of titanium carbide is 1.5wt% of the mass of the nickel-based high-temperature alloy powder, and the first nickel-based high-temperature alloy powder doped with TiC is obtained. According to the laser selective melting molding of Example 3, the nickel-based high-temperature alloy doped with TiC is obtained by laser selective melting molding.
[0114] Fig.12 This is a scanning electron microscope photo of a printed sample of a TiC-doped nickel-based superalloy formed by laser selective melting. Fig.12 It can be seen that there are very fine white carbide particles between dendrites and in cellular crystals. The carbide particles can reach nanometer level. The carbide particles can achieve dispersion strengthening, which corresponds to the excellent tensile mechanical properties.
[0115] The room temperature tensile stress and strain of the printed sample of the TiC-doped nickel-based high-temperature alloy formed by selective laser melting was tested by the method of Example 1. The results showed that the tensile strength of the printed sample of the TiC-doped nickel-based high-temperature alloy formed by selective laser melting was 1479 MPa, and the elongation was 6.2%.
[0116] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A nickel-based high-temperature alloy powder, characterized in that: The invention comprises the following elements in percentage by mass: Cr 8-10%, Co 13-17%, Al 2-5%, W 4-5%, Mo 4-5%, Ti 1-2%, Ta 6-8%, C 0.005-0.1%, B 0.005-0.1% and the balance Ni.
2. The method for preparing the nickel-based high-temperature alloy powder according to claim 1, characterized in that: The following steps are involved: The raw materials are subjected to vacuum smelting to obtain alloy liquid; The alloy liquid is subjected to gas atomization treatment and screening to obtain the nickel-based high-temperature alloy powder.
3. A nickel-based high-temperature alloy, characterized in that: The nickel-based high-temperature alloy is prepared from the nickel-based high-temperature alloy powder according to claim 1 or the nickel-based high-temperature alloy powder prepared by the preparation method according to claim 2.
4. The method for preparing the nickel-based high-temperature alloy according to claim 3, characterized in that: The following steps are involved: The nickel-based high-temperature alloy powder according to claim 1 or the nickel-based high-temperature alloy powder obtained by the preparation method according to claim 2 is used as a raw material, and the nickel-based high-temperature alloy is obtained by laser selective melting molding or laser coaxial powder feeding molding.
5. A TiC-doped nickel-based high-temperature alloy powder, characterized in that: It comprises nickel-based high-temperature alloy powder and titanium carbide powder; the nickel-based high-temperature alloy powder is the nickel-based high-temperature alloy powder according to claim 1 or the nickel-based high-temperature alloy powder prepared by the preparation method according to claim 2.
6. The TiC-doped nickel-based high-temperature alloy powder according to claim 5, characterized in that: The mass of the titanium carbide powder is 0-2% of the mass of the nickel-based high-temperature alloy powder, but not 0%.
7. The method for preparing TiC-doped nickel-based high-temperature alloy powder according to claim 5 or 6, characterized in that: The following steps are involved: The nickel-based high-temperature alloy powder and the titanium carbide powder are mixed at high frequency to obtain the TiC-doped nickel-based high-temperature alloy powder; The acceleration of the high-frequency mixing is 50-100g, and the vibration frequency is 50-60Hz.
8. A TiC-doped nickel-based high-temperature alloy, characterized in that: The powder is prepared from the TiC-doped nickel-based high-temperature alloy powder as claimed in any one of claims 5 to 6 or the TiC-doped nickel-based high-temperature alloy powder prepared by the preparation method as claimed in claim 7.
9. The method for preparing the TiC-doped nickel-based high-temperature alloy according to claim 8, characterized in that: The TiC-doped nickel-based high-temperature alloy powder according to any one of claims 5 to 6 or the TiC-doped nickel-based high-temperature alloy powder prepared by the preparation method according to claim 7 is used as a raw material, and the TiC-doped nickel-based high-temperature alloy is obtained by laser selective melting molding or laser coaxial powder feeding molding.
10. Use of the nickel-based high-temperature alloy powder according to claim 1, the nickel-based high-temperature alloy according to claim 3, the TiC-doped nickel-based high-temperature alloy powder according to any one of claims 5 to 6, or the TiC-doped nickel-based high-temperature alloy according to claim 8 in the fields of aerospace, aviation or energy.